2016
DOI: 10.7705/biomedica.v36i2.2710
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbilidad: bases conceptuales, modelos epidemiológicos y retos de su medición

Abstract: Contribución de los autores:Ambos autores contribuyeron a la concepción y el diseño del ensayo, el análisis y la interpretación de las fuentes originales, así como a la redacción y la aprobación de la versión final. Multimorbilidad: bases conceptuales, modelos epidemiológicos y retos de su mediciónJulián A. Fernández-Niño 1 , Eduardo Bustos-Vázquez 2 1 Centro de Información para Decisiones en Salud Pública, Instituto Nacional de Salud Pública, Cuernavaca, México 2 Escuela de Salud Pública de México, Instituto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
0
11
0
8
Order By: Relevance
“…The presence of multimorbidity was determined according to self-reports of having a medical diagnosis of illnesses from a list of 8 primary chronic diseases (arthritis, cerebrovascular event, angina, diabetes, chronic obstructive pulmonary disease, asthma, hypertension, and cataracts). This variable was characterized as: none or only one morbidity, two morbidities, or three or more (the standard definition of multimorbidity) ( Fernández-Niño & Bustos-Vázquez, 2016 ). Lastly, the history of accidents or physical injuries over the previous 12 months was dichotomized (yes=1 and no =0).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of multimorbidity was determined according to self-reports of having a medical diagnosis of illnesses from a list of 8 primary chronic diseases (arthritis, cerebrovascular event, angina, diabetes, chronic obstructive pulmonary disease, asthma, hypertension, and cataracts). This variable was characterized as: none or only one morbidity, two morbidities, or three or more (the standard definition of multimorbidity) ( Fernández-Niño & Bustos-Vázquez, 2016 ). Lastly, the history of accidents or physical injuries over the previous 12 months was dichotomized (yes=1 and no =0).…”
Section: Methodsmentioning
confidence: 99%
“… 2 , 20 Additionally, the prevalence of simultaneous chronic diseases increases, 2 which is known as multimorbidity. Based on a systematic review of the scientific literature, the European General Practice Research Network identified 132 definitions in 416 papers and established the following definition: “Multimorbidity is defined as any combination of a chronic disease with at least one other disease (acute or chronic) or with a psychosocial factor (associated or not) or with a somatic factor.” 3 Increased multimorbidity leads to polypharmacy, which is the greater use of medical and social services as well as restrictions on activity, making it a public health problem. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis has been reported in association with malnutrition, diabetes, smoking, alcoholism, chronic pulmonary disease, and HIV infection. 13 , 14 The combination of tuberculosis with other diseases, which is now known as “multimorbidity,” 15 is important because it can complicate clinical treatment and increase costs, among other reasons. 14 Given that previous social network analyses of individuals with tuberculosis have not addressed the topic of multimorbidity, the objective of the present study was to explore possible associations between the number of contacts and multimorbidity.…”
mentioning
confidence: 99%